LEGAL CHARACTERISTIC OF COPYRIGHT WHICH IS SUBJECT TO PROTECTION BY THE CIVIL LEGISLATION OF THE RUSSIAN FEDERATION - Marina A. Klimenko (Вестник Северо-Кавказского федерального университета)
Article is devoted to the analysis of the legal nature of the rights of authors on works of science, literature and art. Features of the personal non-property rights, exclusive right to work and other copyright are defined. Other classification of copyright allowing to consider features of these rights and corresponding to legislative division of measures of protection of the intellectual rights is offered.